Problem-based learning with iSpring assisted inquiry method on critical thinking skills - Lestari, Pinta Dewi; Baiduri, Baiduri; Ummah, Siti Khoiruli (Journal of Education and Learning (EduLearn), 2024)
Student’s critical thinking skills that are currently still low are important to develop because they affect the way students think in solving problems. The problem-based learning model with the inquiry method used to help improve student’s critical thinking skills. The iSpring learning media used can help students understand the material. The research results were obtained from the output of the paired sample t-test, a significance value 0.05, so it was concluded that there was a difference between before applying the learning model and after applying the learning model. The results of the questionnaire responses to the media also resulted in positive responses from students.